Penegakan Hukum bagi Pelaku dan Perlindungan Hukum bagi Korban Terkait Sekstorsi dalam Tindak Pidana Korupsi berdasarkan Peraturan Perundang-undangan di Indonesia - Gan, Vannessa; Sewu, Pan Lindawaty Suherman (University of Merdeka Malang, 2023)
In Indonesia, cases of sextortion often occur. Sextortion is the abuse of power to obtain personal gain in the form of sexual activity by coercing the victim so that the victim will experience negative impacts on health or mental health and the victim is also threatened not to report this to the authorities. Both the Sexual Violence Crime Law (hereinafter referred to as the